Divergent knowledge and perceptions of insects by organic and non-organic farming in the Ecuadorian Andes - Cardenas, T.; Teixidor-Toneu, I.; Navarrete, I.; Montufar, R.; Dangles, O. (2025)
Given the critical role of insects in agriculture, studying farmers’ knowledge of entomofauna and its links to crop management is essential. This study explores how such knowledge, in combination with current farming contexts, can shape the barriers and levers of integrated pest and pollinator management to design pollinator-friendly farming systems. We used mixed methods combining ethnoecological and entomological approaches—including field observations, free lists, and semi-structured interviews—to study the diversity of local agricultural insects and farmers’ knowledge in smallholder farming systems in the Ecuadorian Andes and to assess their perceptions and management of agricultural entomofauna. Our results show that organic farmers recognize and categorize more taxa, especially pollinators, than farmers using pesticides who focus more on taxa considered pests and their harmful functions. Our findings highlight the need for a refined approach of integrated pest and pollinator management, recognizing the diversity of roles insects play in agroecosystems. Strengthening awareness among farmers requires not only bridging gaps between scientific and local knowledge but also promoting a greater emphasis on coexistence with insects rather than solely managing them for their functions. By recognizing diverse knowledge systems, our study underscores the urgency of integrating them to ensure more sustainable agriculture in smallholder contexts.